A new era for sterilization based on supercritical CO2 technology - Ribeiro, Nilza (2019)
The increasing complexity in morphology and composition of modern biomedical materials (e.g., soft and hard biological tissues, synthetic and natural‐based scaffolds, technical textiles) and the high sensitivity to the processing environment requires the development of innovative but benign technologies for processing and treatment. This scenario is particularly applicable where current conventional techniques (steam/dry heat, ethylene oxide, and gamma irradiation) may not be able to preserve the functionality and integrity of the treated material. Sterilization using supercritical carbon dioxide emerges as a green and sustainable technology able to reach the sterility levels required by regulation without altering the original properties of even highly sensitive materials. In this review article, an updated survey of experimental protocols based on supercritical sterilization and of the efficacy results sorted by microbial strains and treated materials was carried out. The application of the supercritical sterilization process in materials used for biomedical, pharmaceutical, and food applications is assessed. The opportunity of supercritical sterilization of not only replace the above mentioned conventional techniques, but also of reach unmet needs for sterilization in highly sensitive materials (e.g., single‐use medical devices, the next‐generation biomaterials, and medical devices and graft tissues) is herein unveiled.